Exogenously added BMP-6, BMP-7 and VEGF may not enhance the osteogenic differentiation of human adipose stem cells. (October 2013) - Kyllönen, Laura; Haimi, Suvi; Säkkinen, Janne; Kuokkanen, Hannu; Mannerström, Bettina; Sándor, George K. B.; Miettinen, Susanna
Abstract In the present study bone morphogenetic protein (BMP)-6 alone or in synergy with BMP-7 and vascular endothelial growth factor (VEGF) were tested with human adipose stem cells (hASCs) seeded on cell culture plastic or 3D bioactive glass. Osteogenic medium (OM) was used as a positive control for osteogenic differentiation. The same growth factor groups were also tested combined with OM. None of the growth factor treatments could enhance the osteogenic differentiation of hASCs in 3D- or 2D-culture compared to control or OM. In 3D-culture OM promoted significantly total collagen production, whereas in 2D-culture OM induced high total ALP activity and mineralization compared to control and growth factors groups, but also high cell proliferation. In this study, hASCs did not respond to exogenously added growth although various parameters of the study set-up may have affected these findings contradictory to the previous literature.